Tensile Properties And Electrical Conductivity Of Linear Low-Density Polyethylene (LLDPE)/Carbon Black Conductive Polymer Composites (CPCs) : Effect Of Compounding Parameters - K.A. Abdul Halim; M.A.A. Mohd Salleh; M.M.A Abdullah; A.A. Rozaimi; F. Badrul; A.F. Osman; M.F. Omar; M.S. Zakaria; B. Jeż (Archives of Metallurgy and Materials)
In recent years, the research and development in conductive polymer composites (CPCs) had gained considerable interests in both industry and academia as potential materials for electronic interconnects. These composites require to have the ability to conduct electric while maintaining sufficient flexibility while withstanding the bending, twisting, or stretching during service. To achieve the desired composite properties, the processing method and the parameters involved plays important role and ought to be investigated. In this study, the effect compounding parameters on the preparation of linear-low density polyethylene/carbon black (LLDPE/CB) polymer composite were carried out. Factors namely filler loadings, screw speed and maximum barrel temperatures were selected and their effects on the tensile properties and conductivity were analyzed in this research. It was observed that the increasing of filler loadings from 5 wt.% to 10 wt.% has increased the electrical conductivity from 1.11×10–2 S/m to 1.46×10–2 S/m. The pareto chart shows that the filler loading was important factors to the result of composite conductivity. Moreover, the main effect plot shows that the filler loading has the highest mean effect on conductivity as it is important for the formation of conducting path in composite. It was also established that the pareto chart also shows that filler loading and barrel temperature have the highest significant effect on LLDPE/CB polymer composite tensile properties. The changes in the combinations of factors affect the tensile properties as revealed by the main effect plots for LLDPE/CB CPCs.